Dissolution Profile Comparison:Model Dependent and Model Independent Approaches - SIMA SADRAY; SOHEILA HONARY; POUNEH EBRAHIMI; PARIS JAFARI; SAEED REZAEE (International Journal of Pharma and Bio Sciences, 2010)
Similarity in Dissolution behavior of drugs has long been sought from the percpective of both bioavailability and quality control considrations. The objective of this study was to apply several profile comparison to dissolution data of three different batches of Indomethacin (SR) which two of them were German products as the refernce batches. Dissolution was performed using the United States Pharmacopiea (USP) monograph method on tablets and capsules. Two general approaches to compare dissolution profiles were examined: Model-independent approaches and Model-dependent approaches. The model-independent methods included dissolution efficiency (DE) and the fit factors (F1 and F2). The model-dependent approaches included Weibull and Exponential models. It is concluded that according to the fit factors and model-dependend approaches, the dissolution of test batches are significantly different with one of the reference batches and is almost similar to the other one.